Illogical Framework: The Importance of Monitoring and Evaluation in In ternational Development Studies - Pomerantz, Jessica R. (Cornell Policy Review, 2011)
In my brief experience with monitoring and evaluation, I have become c onvinced that it is critically important both as an international deve lopment project component and as a field of academic study. Throughout my academic career at Cornell University, I have, at times, argued th at monitoring and evaluation has actually impeded development efforts, but here I wish to amend my opinion. Bad monitoring and evaluation ca n sabotage development projects and our meaningful interpretation of d evelopment impacts; failures can appear to be successes and vice-versa . As a student and practitioner of monitoring and evaluation, I have d rawn the conclusions listed below and I submit them for your considera tion. • Monitoring and evaluation is a key element of the internationa l development industry applicable to many areas of public administrati on, domestic and international. • International development failures c ould be discovered and averted or corrected given proper monitoring an d evaluation activities. • Anecdotal evidence from development activit ies in Afghanistan provides one example of the international community ’s lack of attention to monitoring and evaluation concerning an ongoin g development catastrophe. • Higher education ought to be filling the monitoring and evaluation knowledge gap but to date is failing to do s o.